Sympathetic axonal sprouting induces changes in macrophage populations and protects against pancreatic cancer - Jérémy Guillot; Chloé Dominici; Adrien Lucchesi; Huyen Thi Trang Nguyen; Angélique Puget; Mélanie Hocine; Martha M. Rangel-Sosa; Milesa Simic; Jérémy Nigri; Fabienne Guillaumond; Martin Bigonnet; Nelson Dusetti; et al. (Nature Communications, 2022)
The autonomic nervous systems densely innervate the pancreas, but its contribution to pancreatic ductal adenocarcinoma (PDAC) progression is not fully understood. Here, the authors characterize the pattern of sympathetic innervation by 3D imaging in a murine model of PDAC and show that sympathectomy aggravates cancer progression.